Precarity and insecurity in international schooloing new realities and new visions - Bunnell, Tristan (Emerald points, 2021)
The arena of International Schooling is growing rapidly and changing in nature. The number of schools delivering a curriculum wholly or partly in English outside an English-speaking nation reached 12,000 in 2020. China and the Middle East is the emerging centre of activity, and local parents are the main customers